Professor Leif Bjørnø - KOZACZKA, Eugeniusz; STEPNOWSKI, Andrzej (Archives of Acoustics, 2015)
On 24 October 2015 Professor Leif Bjørnø died. Professor Leif Bjørnø was a prominent scientist and a great friend of Polish acousticians.